The application of fractal dimension on capillary pressure curve to evaluate the tight sandstone - Guo, Chunhua; Yang, Yu; Yan, Ping; Zhou, Ruili; Peng, Xiaodong (Penerbit Universiti Kebangsaan Malaysia, 2017)
The rock of gas tight reservoir is more heterogeneous than that of conventional sandstone reservoir and is more prone to water-blockage because of the invasion of operation fluid. This paper presented a new approach for the analysis of the capillary pressure curve for tight gas reservoir. Herein, the saturation equation with fractal dimension proved the previous observation that the log-log plot of capillary pressure against water saturation is a straight line, which is quite different from the popular observation by Corey’s correlation. How to transform the capillary pressure curve to relative permeability curve was also discussed with fractal dimension. The fractal dimension of capillary pressure, which is not only an indication of heterogeneity, can also reveal the potential water blocks in tight gas wells. If the rock has higher fractal dimension, being at the same water saturation, the capillary pressure will be higher and the relative permeability of water will be smaller, which means higher injection pressure is required to displace the trapped water in reservoir. It is suggested that for the tight gas pay zone with higher fractal dimension, more precautions should be taken to prevent the water trapping during drilling or stimulating operation.